Biofilm Pada Otitis Media Supuratif Kronik - Edward, Yan; Novianti, Dini (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2015)
ABSTRACT A number of study find that clinically and complication of Chronic Suppurative Otitis Media (CSOM) related with tipe of bacterial and change of bacterial adherence resulting biofilms. CSOM characterized by purulent discharge from perforated tympanic membrane that occur more than 2 months intermittent or persistent. There was new pattern of bacterial adherence with host. Bacterial adherence result a biofilms. Biofilms is slow growth bacterial colonies and enveloped by glycoplysacaride layer that called glycocalyx. Various methods to detect biofilm are Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Confocal Scanning Laser Microscopy (CSLM) and Calgary Biofilm Device Assay modification, tissue culture plate, tube method and congo red agar. Keywords: Chronic suppurative otitis media, biofilm